UM LABORATÓRIO E UM MUSEU DE EDUCAÇÃO MATEMÁTICA: COLOCANDO A MÃO NA MASSA! - Martensen Roland Kaleff, Ana Maria; Arenari Garcia, Vanessa (LINKSCIENCEPLACE, 2026)
In this article, we consider the reasons that lead us to review the perspective, which we could call hand in hand for educational actions in the classroom and in interactive museum exhibitions.We present some actions that we performed in the Laboratory of Geometry Teaching (LEG) of the Fluminense Federal University, in Niterói-RJ, for the creation of an Interactive Museum of Mathematical Education towards the teacher’s formation for the exercise of a teaching that takes the student to an active inclusive learning also in relation to those with visual impairment (blind or low vision). We finish by reviewing actions already taken, in this perspective, with the Municipal Department of Education of Macaé and outline the outline of what is intended for the future of our actions with this body.